1984
DOI: 10.1159/000225879
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aerobic Glycolysis in Normal and Neoplastic Lymphoid Cells Induced by Lonidamine [1-(2,4-Dichlorobenzyl)-I-H-indazol-3-carboxylic acid]

Abstract: The in vitro inhibitory activity of Lonidamine on the aerobic glycolysis of normal as well as leukemic lymphocytes has been investigated. The extent of the impairment of lactate production induced by Lonidamine on normal thymus (T)- and bone marrow (B)-derived lymphocytes was found to be dependent on their source of origin, i.e. residing or circulating pool. Among leukemia tested ‘null’ and B cell leukemias appeared the most affected metabolically by the compound. Administration in vivo of the drug to the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Interestingly, it seems to enhance aerobic glycolysis in normal cells, but suppresses glycolysis in cancer cells, likely through inhibition of the mitochondrially bound hexokinase (Floridi et al, 1981). Importantly, in vivo administration of lonidamine to a patient with B-cell chronic leukemia resulted in a decrease of lactate production comparable to that observed in vitro (Natali et al, 1984). Subsequent studies in Ehrlich ascites tumor cells showed that lonidamine inhibits both respiration and glycolysis in a dose-dependent manner leading to a decrease in cellular ATP (Floridi et al, 1998).…”
Section: Lonidaminementioning
confidence: 85%
“…Interestingly, it seems to enhance aerobic glycolysis in normal cells, but suppresses glycolysis in cancer cells, likely through inhibition of the mitochondrially bound hexokinase (Floridi et al, 1981). Importantly, in vivo administration of lonidamine to a patient with B-cell chronic leukemia resulted in a decrease of lactate production comparable to that observed in vitro (Natali et al, 1984). Subsequent studies in Ehrlich ascites tumor cells showed that lonidamine inhibits both respiration and glycolysis in a dose-dependent manner leading to a decrease in cellular ATP (Floridi et al, 1998).…”
Section: Lonidaminementioning
confidence: 85%
“…Lonidamine showed benefits in inhibiting glycolysis in cancer cells while increasing glycolysis in nontransformed cells. These pre-clinical studies evidenced Lonidamine as possessing merit as a chemotherapeutic [155,156,157]. Lonidamine reached phase III of clinical trials [158,159,160], however, there has not been further advancement with this agent recently.…”
Section: Implications For Cancer Therapy and Chemopreventionmentioning
confidence: 99%
“…Although the mechanism of action remains unclear, LND treatment is known to target metabolic pathways in cancer cells. Early studies based on reduced secreted lactate claimed that glycolysis was inhibited in LND-treated cells ( 16 , 23 , 24 ). This was proposed to arise through LND-mediated inhibition of mitochondrially bound hexokinase II, the enzyme that catalyzes the phosphorylation of glucose to glucose 6-phosphate once it enters the cell ( 23 ).…”
Section: Introductionmentioning
confidence: 99%